ASSESSMENT OF SPRING WATER POTENTIAL BASED ON WATER BALANCE FOR DOMESTIC WATER SUPPLY IN BESANG KAWAN TOHJIWA VILLAGE - Lucyanita Bayu Risqi; I Made Alit Widnyana; Azizah Azis (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
Besang Kawan Tohjiwa Village Klungkung Regency Bali, has a natural spring with significant potential that has not been optimally utilized for domestic water supply. Currently, the spring is mainly used for drinking water, while other domestic water needs rely on PDAM supply. This study aims to evaluate the capability of the spring to meet domestic water demand based on a quantitative water availability approach. A quantitative descriptive-analytical method was applied. Spring discharge was measured using the volumetric method, while domestic water demand was calculated based on population data and standard domestic water requirements. A water balance approach was used to compare water availability and demand. The results indicate that the spring water availability is 5.61 m³/day, while the domestic water demand is 5.43 m³/day, resulting in a surplus of 0.18 m³/day. Quantitatively, the spring has sufficient capacity to meet domestic water demand. However, its utilization is constrained by the elevation difference between the spring location and residential areas. Proper technical planning of water abstraction and distribution systems is required to enable sustainable and efficient utilization of the spring as an alternative domestic water source.